Metal copper electrode prepared by cold pressing method and application

The formation of a self-supported metal copper electrode with an amorphous structure at room temperature by cold pressing method, solving the problem of insufficient activity and stability of the catalytic electrode in the prior art, and achieving efficient catalytic effect in electrochemical hydrogen evolution reaction.

CN119530849AActive Publication Date: 2025-02-28TIANJIN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411572412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-28
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art lacks high activity, stability and low cost catalytic electrodes, which are difficult to effectively apply in electrochemical hydrogen evolution reactions.

Method used

The copper nanoparticles were pressed in oxygen at room temperature by cold pressing method to form a self-supported metal copper electrode with an amorphous structure. This method combines mechanical force and chemical reactions to simplify the process and reduce costs.

Benefits of technology

The high activity and stability of the copper electrode in the electrochemical hydrogen evolution reaction are achieved, the overpotential at the current density of 10mA/cm2 is reduced, and the catalytic performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530849A_ABST
    Figure CN119530849A_ABST
Patent Text Reader

Abstract

The invention relates to a metal copper electrode prepared through a cold pressing method and application. Metal nano copper powder is used as a raw material; high-hardness stainless steel is adopted as a mold, the weighed powder is poured into a sleeve of the mold, an upper pressing head of the mold is placed into the sleeve, and then an oxygen pipe is led into a side hole channel of the mold; aligning an upper pressing head of the mold to the center of the pressing machine, lowering a pressing head of the hydraulic machine, opening an oxygen valve and introducing oxygen when the hydraulic machine is in contact with the upper pressing head of the mold, and then continuously applying pressure and keeping forming of the metal powder; the oxygen valve is closed while the pressure is unloaded, the pressed and formed metal copper block is taken out through a demolding device, and the taken-out metal copper block is directly used as a catalytic electrode. The prepared metal copper block is directly used as a cathode material for water electrolysis hydrogen production or used for an electrochemical hydrogen evolution reaction; and the overpotential under the current density of 10mA / cm < 2 > can be reduced by more than 50%, and is far higher than that of metal nano-copper particles which are not subjected to cold pressing processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal self-supporting electrode preparation and electrocatalysis, and in particular to the cold pressing method for preparing a highly active amorphous copper electrode for electrochemical hydrogen evolution reaction; specifically, the cold pressing method for preparing a metal copper electrode and its application. Background Art

[0002] Global energy issues have been plaguing mankind since the new century. The growing demand for energy, the continuous depletion of traditional energy, and the environmental problems caused by pollution have prompted people to continuously develop new energy systems that can replace traditional energy. Hydrogen energy, as a clean and sustainable energy source, is expected to replace fossil energy with limited reserves in the next few hundred years. Water electrolysis technology is considered to be an effective method for converting electrical energy into clean, renewable hydrogen energy with high energy density. Among them, alkaline electrolyzer equipment is inexpensive and can effectively avoid acid mist and corrosion, and can be widely used in industrial green hydrogen production. Metal electrocatalysts play a vital role in the field of energy conversion and storage. At present, platinum-based materials are considered to be the most active catalysts because they have the highest exchange current density and the lowest overpotential. However, high prices, low yields, and poor stability severely limit their widespread application.

[0003] Copper metal is abundant in reserves and is a common, low-cost conductive material with the potential to be used in the field of electrocatalysis. 10 The electronic structure of copper and its weak adsorption of hydrogen make it have very poor catalytic activity for hydrogen evolution reaction, see: Zhao J et al.ACS Catal.2015,5,4115. Therefore, few people use copper as a catalyst for hydrogen evolution reaction. In addition, the high surface energy of nanoparticles makes them potentially highly catalytic, but traditional nano-electrochemical catalytic materials require the addition of adhesives during use, and the coated nano-catalysts will fall off, resulting in poor long-term stability. In contrast, electrodes with self-supporting structures are not only stable, but also conducive to industrial use, see: Yang Hetal.Adv.Energy Mater.,2021,11,2102074. In summary, the field of electrochemical hydrogen evolution currently lacks catalytic electrodes with high activity, high stability, low price, and easy large-scale application. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art development, the present invention provides a self-supporting metal copper electrode prepared by cold pressing. That is, in a room temperature environment, copper nanoparticles are pressed in oxygen so that an amorphous structure is formed on the surface of the copper nanoparticles. Compared with the electrocatalysts prepared by spraying (such as Raney nickel, etc.) used in traditional commercial applications, this self-supporting electrode has stronger stability and will not cause catalyst shedding under high current working conditions. In addition, compared with other processes that require harsh conditions to form amorphous structures (such as rapid cooling, high-energy irradiation, etc.), we can combine mechanical force with chemical reaction at room temperature and prepare an amorphous structure using mild reaction conditions. In addition, this amorphous structure exhibits excellent catalytic activity for the electrolysis of water to produce hydrogen. Specifically, compared with metal nano-copper particles that have not been cold pressed, it has a higher catalytic activity at 10mA / cm 2 The overpotential at current density of 1.5 and 2.5 was reduced by more than 50%, which improved the catalytic performance of metal copper nanoparticles. This method of cold pressing metal nanoparticles in the reaction gas, combining mechanical force with chemical reaction to produce an amorphous metal structure with a stable catalytic center, is not only simple in process, low in cost, and easy to industrialize, but also modifies inactive metal copper into a self-supporting hydrogen evolution electrode with high activity.

[0005] The technical solution of the present invention is as follows:

[0006] The cold pressing method of the present invention is used to prepare a metal copper electrode; the cold pressing method comprises the following steps:

[0007] (1) Using metal nano copper powder as raw material;

[0008] (2) Use high-hardness stainless steel as a mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0009] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, and then continue to apply pressure and maintain it to form the metal powder;

[0010] (4) While unloading the pressure, close the oxygen valve and use a demolding device to take out the pressed copper block. The taken-out copper block is directly used as a catalytic electrode.

[0011] The high-hardness stainless steel used as the mold is Cr12.

[0012] The mold consists of an upper pressing head and a sleeve, wherein a hole is opened on the side of the sleeve.

[0013] The pressure required for the upper pressure head is 100MPa-1000MPa; the pressure holding time is 5min-720min.

[0014] The purity of the metal nano copper powder should be greater than 99.9%, and the particle size of the nano copper powder is 50nm-500nm

[0015] The mass of the metal nano copper powder is 2.66*10 -3 D 2 g-5.03*10 -3 D 2 g, where D is the inner diameter of the sleeve in mm.

[0016] The flow rate of oxygen introduced is 3-5L / min.

[0017] The metal copper block prepared by the method of the present invention is directly used as a cathode material for producing hydrogen by electrolyzing water.

[0018] The metal copper electrode prepared by the method of the present invention is used for electrochemical hydrogen evolution reaction.

[0019] Through transmission electron microscopy, it can be observed that an amorphous layer is formed on the surface of copper nanoparticles. Compared with the copper nanoparticles that are completely crystallized before pressing, the amorphous layer on the particle surface is formed during the cold pressing process. The above characterization of the microscopic morphology structure proves that the amorphous layer structure is formed on the surface of the copper nanoparticles during the cold pressing process.

[0020] The copper electrode obtained by cold pressing was subjected to electrochemical hydrogen evolution test, and 1.0 mol / L KOH was used as the electrolyte in the test. The copper electrode was used as the cathode (working electrode) for hydrogen production by electrolysis of water, and was connected to a three-electrode system (working electrode, reference electrode, counter electrode) for testing. During the test, bubbles continued to emerge on the catalyst surface. The copper electrode has excellent electrochemical hydrogen evolution reaction activity, specifically at 10 mA / cm 2 The overpotential at a current density of can be reduced by more than 50%, which is far higher than that of metal nano copper particles that have not undergone cold pressing.

[0021] The present invention has the following advantages:

[0022] We used the cold pressing process to cold press copper nanoparticles in oxygen at room temperature to prepare amorphous copper electrodes for electrocatalytic hydrogen evolution reaction in alkaline solutions. In particular, the amorphous structure formed on the surface of the particles gives them excellent hydrogen evolution reaction activity, reducing the thermodynamic and kinetic barriers during the reaction. The copper electrode catalyst formed by cold pressing is superior to metal nano-copper particles that have not been cold pressed in alkaline solutions, and even superior to previously reported copper-based catalysts. The rapid preparation of highly active amorphous copper catalysts has opened up a new way to produce green and clean hydrogen energy by electrolysis of water. Metallic copper resources are abundant and inexpensive; the cold pressing process is simple, convenient and fast, and metal electrode materials can be quickly prepared; no toxic raw materials and reagents are used in the entire preparation process, which is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Diagram of the process equipment for preparing amorphous copper electrodes by cold pressing.

[0024] Figure 2 This is a high-magnification transmission electron microscope image of the cold-pressed copper electrode (Cu1) obtained in Example 1.

[0025] Figure 3 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu1) obtained in Example 1.

[0026] Figure 4 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu2) obtained in Example 2.

[0027] Figure 5 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu3) obtained in Example 3.

[0028] Figure 6 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu4) obtained in Example 4.

[0029] Figure 7 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu5) obtained in Example 5.

[0030] Figure 8 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu6) obtained in Example 6.

[0031] Fig. 9 This is a polarization curve diagram of the hydrogen evolution reaction of the cold-pressed copper electrode (Cu7) obtained in Example 7.

[0032] Fig.10 Polarization curve of hydrogen evolution reaction of commercial metal nanocopper powder (Cu NPs). DETAILED DESCRIPTION

[0033] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The following embodiments can enable the professional and technical personnel to understand the present invention more comprehensively, but do not limit the present invention in any way.

[0034] Supplement the embodiments according to the conditions of the invention content to prove that all ranges of conditions can realize the invention, and verify all embodiments and specific conditions and effects

[0035] Embodiment 1:

[0036] (1) Using metal nano copper powder as raw material, the purity is greater than 99.9% and the diameter is 50nm. Taking the inner diameter of the sleeve D = 13mm as an example, according to 2.66*10 -3 D 2 g~5.03*10 -3 D 2 g calculation, at this time the mass range of nano copper powder is 0.45g-0.85g, take 0.45g powder;

[0037] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0038] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 5L / min, and then continue to apply pressure to 500MPa and maintain it at this pressure for 5min;

[0039] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0040] The sample obtained in Example 1 is recorded as Cu1. Figure 2 This is a high-magnification transmission electron microscope image of Example 1. From the figure, it can be seen that the outer layer of the copper nanoparticles in Example 1 presents an obvious amorphous structure. The above results all show that a layer of amorphous structure is formed on the surface of Example 1.

[0041] The LSV polarization curve of Example 1 tested in 1.0 mol / L KOH solution is shown in Figure 3 , it can be seen that Example 1 at 10mA / cm 2 The overpotential after 90% IR correction at current density is 96mV. Fig.10Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 75.5%.

[0042] Embodiment 2:

[0043] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 50 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.45 g of powder is taken;

[0044] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0045] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 4L / min, and then continue to apply pressure to 100MPa and maintain it at this pressure for 5min;

[0046] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0047] The sample obtained in Example 2 is recorded as Cu2. The LSV polarization curve of Example 2 tested in 1.0 mol / L KOH solution is shown in Figure 4 It can be seen that Example 2 has a 2 The overpotential after 90% IR correction at the current density is 134mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 65.8%.

[0048] Embodiment 3:

[0049] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 50 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.45 g of powder is taken;

[0050] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0051] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 4L / min, and then continue to apply pressure to 500MPa and maintain it at this pressure for 120min;

[0052] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0053] The sample obtained in Example 3 is recorded as Cu3. The LSV polarization curve of Example 3 tested in 1.0 mol / L KOH solution is shown in Figure 5 , it can be seen that Example 3 at 10mA / cm 2 The overpotential after 90% IR correction at the current density is 136mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 65.3%.

[0054] Embodiment 4:

[0055] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 50 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.65 g of powder is taken;

[0056] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0057] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 3L / min, and then continue to apply pressure to 1000MPa and maintain it at this pressure for 120min;

[0058] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0059] The sample obtained in Example 4 is recorded as Cu4. The LSV polarization curve of Example 4 tested in 1.0 mol / L KOH solution is shown in Figure 6 It can be seen that Example 4 has a 2 The overpotential after 90% IR correction at the current density is 139mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 64.5%.

[0060] Embodiment 5:

[0061] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 50 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.85 g of powder is taken;

[0062] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0063] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 3L / min, and then continue to apply pressure to 1000MPa and maintain it at this pressure for 720min;

[0064] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0065] The sample obtained in Example 5 is recorded as Cu5. The LSV polarization curve of Example 5 tested in 1.0 mol / L KOH solution is shown in Figure 7 It can be seen that Example 5 at 10mA / cm 2 The overpotential after 90% IR correction at current density is 155mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 60.5%.

[0066] Embodiment 6:

[0067] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 200 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.65 g of powder is taken;

[0068] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0069] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 5L / min, and then continue to apply pressure to 1000MPa and maintain it at this pressure for 5min;

[0070] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0071] The sample obtained in Example 6 is recorded as Cu6. The LSV polarization curve of Example 6 tested in 1.0 mol / L KOH solution is shown in Figure 8 It can be seen that Example 6 has a 2 The overpotential after 90% IR correction at current density is 160mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 59.2%.

[0072] Embodiment 7:

[0073] (1) Using metal nano copper powder as raw material, the purity of which is greater than 99.9% and the diameter is 500 nm. Taking the inner diameter of the sleeve D = 13 mm as an example, the mass range of the nano copper powder is 0.45 g-0.85 g, and 0.85 g of powder is taken;

[0074] (2) Use high-hardness Cr12 stainless steel with compression resistance and corrosion resistance as the mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold;

[0075] (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, control the oxygen flow rate to 5L / min, and then continue to apply pressure to 1000MPa and maintain it at this pressure for 5min;

[0076] (4) After the timing is over, the pressure is unloaded and the oxygen valve is closed. The pressed copper block is taken out using a demolding device. The taken-out copper block can be directly used as a catalytic electrode, such as Figure 1 shown.

[0077] The sample obtained in Example 7 is recorded as Cu7. The LSV polarization curve of Example 7 tested in 1.0 mol / L KOH solution is shown in Fig. 9 , it can be seen that Example 7 at 10mA / cm 2 The overpotential after 90% IR correction at the current density is 191mV. Fig.10 Compared with the commercial metal nanocopper particles measured in , the overpotential was reduced by 51.3%.

[0078] In summary, cold pressing of copper nanoparticles in oxygen at room temperature creates an amorphous structure on the surface of metal nanoparticles. In 1.0 mol / L KOH solution, it has excellent hydrogen evolution reaction activity at 10 mA / cm 2 The overpotential at current density can be reduced by more than 50%, which is much higher than that of metal nano copper particles that have not been cold pressed. This low-cost, high-catalytic activity catalytic electrode has a wide range of application scenarios.

[0079] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. Preparation of metal copper electrode by cold pressing method; characterized in that: The steps include: (1) Using metal nano copper powder as raw material; (2) Use high-hardness stainless steel as a mold, pour the weighed powder into the sleeve of the mold, place the upper pressure head of the mold into the sleeve, and then pass the oxygen tube into the side channel of the mold; (3) Align the upper pressure head of the mold with the center of the press, lower the pressure head of the hydraulic press, and when the hydraulic press contacts the upper pressure head of the mold, open the oxygen valve and introduce oxygen, and then continue to apply pressure and maintain it to form the metal powder; (4) While unloading the pressure, close the oxygen valve and use a demolding device to take out the pressed copper block. The taken-out copper block is directly used as a catalytic electrode.

2. The preparation method according to claim 1, characterized in that: The high hardness stainless steel used for the mold is Cr12.

3. The preparation method according to claim 1, characterized in that: The mold consists of an upper pressing head and a sleeve, wherein a hole is opened on the side of the sleeve.

4. The preparation method according to claim 3, characterized in that: The pressure required for the upper pressure head is 100MPa-1000MPa; the pressure holding time is 5min-720min.

5. The preparation method according to claim 3, characterized in that: The purity of the metal nano copper powder should be greater than 99.9%, and the particle size of the nano copper powder is 50nm-500nm.

6. The preparation method according to claim 3, characterized in that: The mass of metal nano copper powder is 2.66*10 -3 D 2 g-5.03*10 -3 D 2 g, where D is the inner diameter of the sleeve in mm.

7. The preparation method according to claim 3, characterized in that: The flow rate of oxygen is 3-5L / min.

8. The metal copper block prepared by the method of claim 1 is directly used as a cathode material for producing hydrogen by electrolysis of water.

9. The metal copper electrode prepared by the method of claim 1 is used for electrochemical hydrogen evolution reaction.

Citation Information

Patent Citations

  • Preparation method of integrated porous catalytic electrode

    CN117626322A

  • Manufacture of electrode for vacuum interrupter

    JP1993314868A

  • Copper alloy powder for laminate molding, method for producing laminate molding and laminate molding

    JP2019035134A

  • Porous catalyzed electrode provision and technique

    US4187350A